Don't spam if you will spam then i will report
if u will answer 50 points plus brainliest
Attachments:
![](https://hi-static.z-dn.net/files/d4b/4cd4b391833ecbd57f88c22977fb6210.jpg)
Answers
Answered by
2
Answer:
heya
here:alpha+beta=-5 (given)
alpha.beta=3 (given)
applying, x2-(sum of zeros)x+product of zeros
thus the polynomial formed=x^2-(-5)x+3
answer=x^2+5x+3
hope it helps ✌
Answered by
0
Given, Sum of Zeroes= -5
Product of Zeroes= 3
We know that,
Equation of quadratic polynomial=>
So, required equation is
=>
This is the best possible answer
Similar questions